Does Section 7 of the Charter Protect the Right to be a Professional? - Grey, Julius (Les Cahiers de droit, 1990)
This essay deals with the controversy concerning the limits of sec. 7 of the Canadian Charter of Rights and Freedoms. Given that it does not bestow an untrammelled right to practise a profession, does this mean that all matters in the professional field are totally excluded ? In Wilson v. Medical Services Commission, the B.C. Court of Appeal left a role for sec. 7 in professional matters. The decision has been contested by at least one commentator. The main thrust of this essay is to defend Wilson.